Prevalence and Epidemiological Patterns of Entamoeba histolytica Infection among Children in Western Libya: A Comparative Study of 2023 and 2024 (Comprehensive Journal of Science, 2025)
Background: Amebiasis is an intestinal infection caused by the protozoan Entamoeba histolytica.  The infection mainly spread through the fecal-oral route, infected food and water, and bad hygiene. Aim: The study aimed to assess the prevalence of Entamoeba histolytica among children in Western Libya during 2023 and 2024, using data collected from some laboratories. Methods: A total of 250 cases with ages ranging from one month to 14 years were included. Statistical analysis was performed using the chi-square (χ²) test in SPSS software (version 26.0, IBM Corp., Armonk, NY). A significant level of < 0.05 was used to assess the associations between the number of Entamoeba histolytica infections and variables such as number of cases, month, and gender. Results: In 2023, the overall cases were 104. The highest infection rates occurred during the warmer months, particularly in May (18 cases, 17%) and June (18 cases, 17%). A significant monthly variation was observed based on the Chi-squar test (χ² = 32.86, p-value = 0.0007). In contrast, in 2024, the total number of cases increased to 146, which represents to a 40% increase compared to the previous year. The highest number of infections was recorded during the cold months, with November (24 cases, 16%) and December (30 cases, 20%). The Chi-squar test (χ² = 28.77) p-value showed statistically significant variation across months (P < 0.05). Males were slightly more affected than females, accounting for about 58% of cases, however, there was no significant association between gender and infection rates in both years (2023: χ² = 2.31, p = 0.128; 2024: χ² = 3.42, p = 0.064). Most of the affected children were under 14 years of age, with a few newborn children who were 1 month old becoming infected. In 2024, there was a noticeable change, with the majority of infections occurring during the colder months, whereas in 2023, the majority of cases occurred during the warmer months. Conclusion: The results indicate that infections are on the rise and no longer solely occur on the warmer months as previously believed. In order to protect children during is a critical requirement for improved awareness, hygiene practices, and early prevention initiatives.
Keywords: Amebiasis, Entamoeba histolytica (E. histolytica), Children, Western Libya